2015
DOI: 10.3390/ijerph121012340
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Leptin on Breastfeeding Behaviour

Abstract: Breastfed infants have a reduced risk of becoming overweight and/or obese later in life. This protective effect has been partly attributed to leptin present in breastmilk. This study investigated 24-h variations of skim milk leptin and its relationship with breastmilk macronutrients and infant breastfeeding patterns. Exclusive breastfeeding mothers of term singletons (n = 19; age 10 ± 5 weeks) collected pre- and post-feed breastmilk samples for every breastfeed over a 24-h period and test-weighed their infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 64 publications
3
33
0
3
Order By: Relevance
“…Articles | Cannon et al This study failed to show a relationship between skim milk leptin concentration and dose of leptin delivered at a breastfeed and the rate of GE or the time between the feeds. This agrees with our previous study, which did not find an association between skim milk leptin dose and the time between the feeds across a 24-h period (20). Milk leptin has been shown to be biologically active and enter the circulation (15), whereby satiety may be affected via signaling to the hypothalamus to reduce food intake (21).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Articles | Cannon et al This study failed to show a relationship between skim milk leptin concentration and dose of leptin delivered at a breastfeed and the rate of GE or the time between the feeds. This agrees with our previous study, which did not find an association between skim milk leptin dose and the time between the feeds across a 24-h period (20). Milk leptin has been shown to be biologically active and enter the circulation (15), whereby satiety may be affected via signaling to the hypothalamus to reduce food intake (21).…”
Section: Discussionsupporting
confidence: 92%
“…HM is both a unique and dynamic fluid with superior composition, the components of which vary between feeds within women and between women (18)(19)(20). When infants breastfeed on demand and thereby control their nutrient intake (2), it is plausible that their GE pattern could be influenced by milk composition.…”
mentioning
confidence: 99%
“…In addition, the majority of studies that examined associations also found a positive correlation between maternal BMI and/or fat mass and HM fat concentration, providing further support of higher levels of fat in HM in women with a higher BMI. The fat concentration of HM is known to be highly dynamic, varying both across the day and even within a feed [51,52], however the role of external factors in regulating fat synthesis in the breast are not as well understood [43]. It is possible that the metabolic dysregulation commonly reported in women with a higher maternal BMI/fat mass, in particular dyslipidemia and higher circulating triglyceride levels, was associated with an increase in the fat concentration of HM [32].…”
Section: Discussionmentioning
confidence: 99%
“…Further to this, the quality of the included studies was generally low, and there was a lack of standardization of collection methods and procedures. Physiological and methodological aspects of HM, such as gestational age, method, and time of collection, can significantly influence macronutrient levels [51,52,69] and therefore affect the results of comparisons/associations in individual studies. For instance, fat concentration in HM increases significantly (up to three-fold) from the beginning to the end of a breastfeed or expression [70].…”
Section: Discussionmentioning
confidence: 99%
“…Standards were selected according to previous literature investigating levels of leptin in skim human milk, as well as recommendations provided by the leptin kit manufacturer [36]. …”
Section: Figurementioning
confidence: 99%